Implementing Information Literacy (IL) into STEM Writing Courses: Effect of IL Instruction on Students’ Writing Projects at an Urban Community College - Miseon Kim; Mercedes Franco; Dugwon Seo (Issues in Science and Technology Librarianship)
The purpose of this study was to implement information literacy (IL) into Science, Technology, Engineering, and Mathematics (STEM) writing courses at an urban community college, investigate if students’ information literacy (IL) skills were improved through library one-shot instruction, and determine if there was an association between IL skills and students’ writing performance. Students in the experimental group attended the library instructional class and students in the control group had no library class. Students’ research papers were scored using the Association of American Colleges & Universities (AAC&U) Information Literacy VALUE Rubric to grade the effectiveness of the library instruction. While the scores of the papers did not differ between groups, data indicated that there was a statistically significant difference (p = .011) in IL scores between students in the experimental group (M = 9.70) and students in the control group (M = 8.73). The results also showed that information literacy skills were correlated positively with students’ grades on research papers (p = .002).